PENGARUH TARIF RAWAT INAP DAN STANDAR PELAYANAN MINIMAL TERHADAP KEPUASAN PASIEN BPJS DI RUMAH SAKIT SILOAM PURWAKARTA - Rizal Taufik (Media Bina Ilmiah, 2024)
Effect of Inpatient Rates and Minimum Service Standards on BPJS Patient Satisfaction at Siloam Hospital Purwakarta.Based on optimal Service delivery, a health Service institution provides an impetus for the government to make a regulation regarding equitable standards in the health Service system. This study aims to determine how the influence of minimum Service rates and standards in Siloam Purwakarta hospitals in accordance with existing regulations.The analytical framework used is the inpatient tariff framework and minimum Service standards for patient satisfaction evaluating comfort, patient relationships, staff technical competencies and costs. The analytical method used is descriptive analysis with a quantitative approach.The results of the analysis show (1) Effect of Inpatient Rates on Patient Satisfaction partially has a significant influence on patient satisfaction (2) Effect of Minimum Service Standards on Patient Satisfaction partially has a significant effect on patient satisfaction (3) Effect of Inpatient Rates and Standards Minimal Service to patient satisfaction simultaneously has a significant effect on patient satisfaction and has an influence of 90.6% and the remaining 9.4%> is influenced by other factors not examined. The suggestions given by the authors include: (1) It should be noted again about BPJS hospitalization rates and re-socialization about class promotion programs, namely by analyzing the making of hospitalization rates and making special fields for Information on Service rates. (2) Need to continuously provide an explanation or understanding to patients of the minimum Standard of hospitalization. (3) Due to the simultaneous influence between inpatient rates and minimum Service standards on patient satisfaction, the quality of the two variables must be reviewed.